A review on aerodynamics and hydrodynamics in sports. (February 2019) - Alam, Firoz; Chowdhury, Harun; Moria, Hazim
Abstract: Aero/hydrodynamics plays a vital role in speed sports (athletes, athletes' outfits, sports balls, sports equipment, etc.). Sports balls (spherical - golf, cricket, tennis, soccer, baseball, softball, etc. and oval shape - rugby, American football, Australian football), sports garments (swimsuits, ski jumping & alpine skiing suits, cycling skin suits, skating suits) are affected by aerodynamic and hydrodynamic behavior of fluids (air and liquids). The aero/hydrodynamics dictates the curved flight path of a soccer, tennis, cricket, baseball or golf ball and the course of a surfboard and sailboat through water. It affects speed, motion (position and placement) and ultimately athlete's performance. Ignoring the effect of aerodynamic and hydrodynamics, it is almost impossible to achieve the desired success in any competitive speed sports. Due to stiff competition, the outcome of most sports aero/hydrodynamics research work undertaken by commercial organizations as well as individual sports teams/organizations are kept in-house, and scant information is available in the public domain. The RMIT University's Sports Aerodynamics Research Group has been active in aerodynamics and hydrodynamics research related to some popular speed sports. This paper highlights some research work on sports aerodynamics and hydrodynamics undertaken at RMIT University